PENGARUH INTENSITAS ASET TETAP, UKURAN PERUSAHAAN, DAN PERTUMBUHAN PENJUALAN TERHADAP TAX AVOIDANCE (Studi Empiris pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023) - Moses Brugman; Anis Chariri (Diponegoro Journal of Accounting, 2025)
This study aims to investigate the effect of fixed asset intensity, company size, and sales growth on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The dependent variable is tax avoidance, measured using the Cash Effective Tax Rate (CETR). The independent variables include fixed asset intensity (ratio of fixed assets to total assets), company size (natural logarithm of total assets), and sales growth (percentage change in annual sales). This empirical research utilizes secondary data from annual financial reports of energy sector companies listed on the IDX. A purposive sampling method was applied, resulting in 84 observations from 44 companies. Data analysis was conducted using multiple linear regression.The findings reveal that fixed asset intensity and sales growth have a significant negative effect on tax avoidance, indicating that higher fixed asset investments and sales growth reduce tax avoidance practices. Conversely, company size has a positive and significant effect on tax avoidance, suggesting that larger companies are more likely to engage in tax avoidance strategies. These results highlight the complex dynamics of tax planning in the energy sector, emphasizing the role of asset structure, operational scale, and revenue trends in shaping corporate tax behavior.